2015
DOI: 10.1128/mcb.00811-15
|View full text |Cite
|
Sign up to set email alerts
|

The Stationary-Phase Cells of Saccharomyces cerevisiae Display Dynamic Actin Filaments Required for Processes Extending Chronological Life Span

Abstract: Stationary-growth-phase Saccharomyces cerevisiae yeast cultures consist of nondividing cells that undergo chronological aging. For their successful survival, the turnover of proteins and organelles, ensured by autophagy and the activation of mitochondria, is performed. Some of these processes are engaged in by the actin cytoskeleton. In S. cerevisiae stationary-phase cells, F actin has been shown to form static aggregates named actin bodies, subsequently cited to be markers of quiescence. Our in vivo analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 70 publications
1
21
0
Order By: Relevance
“…Such data indicate that clove leaf extract is likely capable of modulating oxidative stress response in a way that is more effective than CR conditions. A previous study had reported that in addition to the autophagy and mitochondrial activities, the dynamic actin cytoskeleton is involved in the survival of stationary phase, thus extending the life span of the yeast S. cerevisiae [28]. To our knowledge, this is the first report of the use of clove leaf extract to promote cell viability of yeast cells, which suggest its potential as an antiaging agent.…”
Section: Resultsmentioning
confidence: 87%
“…Such data indicate that clove leaf extract is likely capable of modulating oxidative stress response in a way that is more effective than CR conditions. A previous study had reported that in addition to the autophagy and mitochondrial activities, the dynamic actin cytoskeleton is involved in the survival of stationary phase, thus extending the life span of the yeast S. cerevisiae [28]. To our knowledge, this is the first report of the use of clove leaf extract to promote cell viability of yeast cells, which suggest its potential as an antiaging agent.…”
Section: Resultsmentioning
confidence: 87%
“…We have previously reported that upon carbon source exhaustion, the actin cytoskeleton reorganizes into Actin Bodies (AB) and the proteasome re-localizes from the nucleus into proteasome storage granules (PSG) ( Sagot et al, 2006 ; Laporte et al, 2008 ; Laporte et al, 2015 ). Whether these rearrangements are specific of the quiescent state has been challenged ( Vasicova et al, 2015 ), but never tested directly. To tackle this question, we used our individual cell tracking approach with cells expressing both Ilv3-RFP and either Abp1-3xGFP (AB) or Scl1-3xGFP (PSG).…”
Section: Resultsmentioning
confidence: 99%
“…Since the sources of energy and materials are restricted in stationary phase cells, formation of protein granules is often regarded as a mechanism to store crucial proteins that will later be used for mitosis re-entry (Laporte et al, 2008;Narayanaswamy et al, 2009;Sagot et al, 2006). However, a few recent studies indicate that some granule structures only appear in cells with inferior physiological states (Lee et al, 2016;Vasicova et al, 2015), suggesting that the storage model is oversimplified. In log phase cells, misfolded or damaged proteins are often collected to specific compartments or deposition sites.…”
Section: Introductionmentioning
confidence: 99%